Accumulation measurements from stake farm Neumayer II, Ekström Ice Shelf, Antarctica, 2003 - Valerie Reppert; Johannes Kässbohrer; Olaf Eisen; Rolf Weller; Zsófia Jurányi (PANGAEA, 2025)
This publication series contains the accumulation measurements from stake farm Neumayer II on the Ekström Ice Shelf, Antarctica. The stake farm (70°39 extquotesingle31 extquotesingle extquotesingleS, 8°15 extquotesingle9W), has been in operation since March 1992. It consists of 25 poles (balise), placed in a grid of 5 x 5 with 10 m spacing. Readings have been carried out in approx. weekly intervals by the overwintering staff. Each data set in the series contains all measurements of each stake from one calendar year in a tsv file, the average accumulation of the stake farm for each measurement and the standard deviation of the stake farm for each measurement. The data sets are accompanied by figures illustrating the development of the cumulative accumulation since the beginning of the measurements to date, a bar chart of the monthly accumulation for the year and a collection of panels (one panel per measurement) illustrating the variation of accumulation within the stake farm.
In: Reppert, Valerie; Eisen, Olaf; Weller, Rolf; Jurányi, Zsófia (2025): Time series of accumulation measurements from stake farm Neumayer II, Ekström Ice Shelf, Antarctica, March 1992 - 2009 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.987098